Ten‐year publication trends in dermatology in mainland China. (22nd August 2013) - Xin, Shujun; Mauro, Jacqueline A.; Mauro, Theodora M.; Elias, Peter M.; Man, Mao‐Qiang
Abstract Background China has been experiencing huge changes in all aspects, including dermatologic research, since its reform in 1978. However, it is not known how the economic and intellectual development has influenced the publication trends in the field of dermatology, which could mirror the scientific development in other medical disciplines. In the present study, we analyzed publication trends from dermatology departments in mainland China from 2002 to 2011. Methods All publication data were obtained from www.pubmed.com. Only papers published from dermatology departments in mainland China were used for analysis. Results The number of publications increased 10‐fold over this 10‐year period. A total of 1231 articles were published in English in 251 journals between 2002 and 2011. A total of 129 journals published only one paper from dermatology departments in mainland China. Over 60% of articles were original research, and 21.7% were case reports. Among these 251 journals, foremost was the Journal of Clinical Experimental Dermatology, which published 5.9% of all papers from mainland China; 2.7% of papers were published in the Journal of Investigative Dermatology. The number of publications positively correlated with the changes in gross domestic product per capita during the study period. Conclusions These results suggest that the number of publications in the dermatology field has increased markedly in mainland China over the last 10 years. This dramatic increase in publications could be attributed, at least partially, to the significant improvement in economic conditions in mainland China.